Evaluation Of Water Delivery Performance In The Paya Sordang Irrigation Area, Padang Sidimpuan Tenggara District, Tapanui Regency - Andri Kurnia Nasution (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2022)
Irrigation plays a role in increasing crop production, by regulating, providing water needs for plants. Water demand for plants is affected by water loss due to decreased performance of irrigation networks. For this reason, a good irrigation system is needed so that water needs for plants can be met. Loss of water that occurs in irrigation canals can affect the efficiency of water requirements needed by plants. To increase crop production, it can also be done by optimizing the available land so that land use becomes more effective. The location of the research study is in the Paya Sordang Irrigation Area, Southeast Padangsidimpuan District, South Tapanuli Regency. Analysis of irrigation water needs was carried out using the FJMock method, from the analysis of irrigation water needs it was found that the mainstay discharge of the Batang Angkola watershed was obtained in order to obtain a good planting pattern and period. From the measurement of the discharge can be seen the efficiency of the irrigation canal. Meanwhile, to calculate land effectiveness, it is done by dividing the irrigated area by the design area. Based on this research, the mainstay discharge is 17.75 m3/s and the water demand is 0.7 lt/sec/ha. The efficiency of the secondary network is 91.1962%, this efficiency has met the efficiency specified in the criteria for irrigation planning, namely for the secondary channel, the efficiency is 90%. From the research results, it can be seen that Paya Sordang irrigation is currently less effective. This can be seen from the initial planned irrigation area which is 4,350 ha and which can be irrigated only 1,232 ha during the dry season and 3,118 during the rainy season, so that the effectiveness of Paya Sordang irrigation is only 28.322% during the dry season and 71.678% during the rainy season.